Effects of cold storage and 1-methylcyclopropene treatments on ripening and cell wall degrading in rabbiteye blueberry (Vaccinium ashei) fruit - Deng, Jia (Food science and technology international = Ciencia y tecnologia de los alimentos internacional, 2014)
The effect of postharvest 1-methylcyclopropene and/or cold storage application on texture quality parameters during storage was determined. The changes in fruit quality (including weight loss, firmness, total soluble solids content, and ethylene production), cell wall material (including water-soluble fraction, ethylenediaminetetraacetic acid-soluble fraction, Na2CO3-soluble fraction, 4% KOH-soluble fraction, and 14% KOH-soluble fraction), and cell wall hydrolase activities (including polygalacturonase, endo-1,4-beta-D-glucanase, pectinesterase, alpha-L-arabinofuranosidase, and beta-galactosidase) were periodically measured up to 25 days after postharvest treatments. The application of cold storage reduced weight loss, ethylene production, and delayed ripening of blueberry fruit. The inhibition of senescence was associated with suppressed increase in cell wall hydrolase activities and retarded solubilization of pectins and hemicelluloses. Furthermore, no obvious differences in firmness, weight loss, ethylene production, and cell wall hydrolase activities between fruits with or without 1-methylcyclopropene application were observed, while significant lower levels of the detected parameters were found in cold storage fruit compared with fruit stored in room temperature. Thus, cold storage can be viewed as an effective means to extend the shelf life of blueberry fruit